2018
DOI: 10.1542/peds.2017-3432
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Diagnoses and Weight Loss Among Adolescents Receiving Sleeve Gastrectomy

Abstract: Psychiatric diagnoses are prevalent among adolescents with severe obesity. These diagnoses are not associated with weight loss outcomes. The presurgical psychological evaluation serves as an opportunity to identify adolescents experiencing psychiatric problems and provide them with care but should not necessarily be considered a contraindication to surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 46 publications
(38 reference statements)
1
16
1
Order By: Relevance
“…The three available studies on the prevalence of ADHD in adolescents seeking MBS reported widely variable results. An Israeli study reported an ADHD prevalence of 28.6% in this population, 9 one American study reported only a 6% prevalence of ADHD, 10 and the other American study reported that 21% of adolescent MBS patients met the criteria for an ADHD diagnosis 11 …”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The three available studies on the prevalence of ADHD in adolescents seeking MBS reported widely variable results. An Israeli study reported an ADHD prevalence of 28.6% in this population, 9 one American study reported only a 6% prevalence of ADHD, 10 and the other American study reported that 21% of adolescent MBS patients met the criteria for an ADHD diagnosis 11 …”
Section: Introductionmentioning
confidence: 84%
“…An Israeli study reported an ADHD prevalence of 28.6% in this population, 9 one American study reported only a 6% prevalence of ADHD, 10 and the other American study reported that 21% of adolescent MBS patients met the criteria for an ADHD diagnosis. 11 ADHD presents in three different ways: combined presentation (deficits in both attention and hyperactivity-impulsivity), predominantly inattentive presentation, previously referred to as attention-deficit disorder (ADD) and predominantly hyperactive/ impulsive presentation. 12 It is not known which, if any, of these presentations are more common in adolescents with severe obesity seeking MBS.…”
Section: Introductionmentioning
confidence: 99%
“…Recommendations suggest that significant psychiatric disorders including severe or unstable psychosis and major depressive disorder should be contraindications to bariatric surgery, though few studies have assessed the influence of psychiatric disorders on outcomes after bariatric surgery among adolescents [97,98]. A recent study found that 71% of adolescents who completed a presurgical psychological evaluation for laparoscopic sleeve gastrectomy qualified for a psychiatric disorder with the most common diagnoses being depression (42%) and anxiety (26%) [99]. None of the psychiatric diagnoses predicted percent excess weight loss at 12 months postsurgery.…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…Hence, when comparing the prevalence of ADHD between populations, the diagnostic methods should be carefully considered. A study that assessed the prevalence of ADHD among adolescents seeking bariatric surgery was published only recently, used semi‐structured clinical interviews and reported a prevalence of 21% …”
Section: Introductionmentioning
confidence: 99%
“…16 It remains unknown whether the presence of ADHD would affect weight loss and other clinical outcomes in adolescents following bariatric surgery. In the study by Mackey et al, 16 ADHD diagnosis was not related to weight change after bariatric surgery, as previously found in adults. 15,17 However, there is evidence that the presence of behavioural traits associated with ADHD at the time of treatment, such as impulsivity, inattention or hyperactivity, might still be a barrier to successful weight loss during conservative obesity treatment.…”
mentioning
confidence: 99%